P(X=k)= p(1-p)^k-1 k=1,2,3....

0 elesewhere

Show that Mx(t)= pe^t

1-(1-p)e^t for t=( -infinity, ln 1/1-p)

I know mgf is intergration of e^fx*fx(x) dx

please help thanx in advance

Printable View

- Jan 28th 2010, 01:24 AMHyungminAbout Moment generating function
P(X=k)= p(1-p)^k-1 k=1,2,3....

0 elesewhere

Show that Mx(t)= pe^t

1-(1-p)e^t for t=( -infinity, ln 1/1-p)

I know mgf is intergration of e^fx*fx(x) dx

please help thanx in advance - Jan 28th 2010, 03:23 AMmr fantastic
Read this: http://www.mathhelpforum.com/math-he...97251-mgf.html

Thread closed.